2021
DOI: 10.24018/ejedu.2021.2.6.220
|View full text |Cite
|
Sign up to set email alerts
|

ESL Teachers’ Professional Development on Facebook During the Covid-19 Pandemic

Abstract: Schoolteachers and college instructors from around the world can create or join special Facebook pages (FPs), groups, or clubs for ESL teachers for free. Those FPs are online learning communities that provide opportunities for in-depth peer-to-peer interaction, communication, and support. This study aims to give examples of FPs for ESL teachers; identify the kinds of topics and issues posted about the teaching and learning of English as a second/foreign language; find out whether there are special ESL Teachers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Whereas during the post-lockdown period (the new normal), it related more toward supporting their TPD (seeking pedagogical advice) and creating their educational content and materials. Another example of using social networks during pandemic times and beyond (new normal) is the proliferation of Facebook pages of groups of teachers that create a common space online to serve TPD's immediate needs and create support during the needed reorganization of teaching and learning activities [2,25,26].…”
Section: Teacher Professional Development Through Peer Learning and P...mentioning
confidence: 99%
“…Whereas during the post-lockdown period (the new normal), it related more toward supporting their TPD (seeking pedagogical advice) and creating their educational content and materials. Another example of using social networks during pandemic times and beyond (new normal) is the proliferation of Facebook pages of groups of teachers that create a common space online to serve TPD's immediate needs and create support during the needed reorganization of teaching and learning activities [2,25,26].…”
Section: Teacher Professional Development Through Peer Learning and P...mentioning
confidence: 99%
“…Ying et al (2021) stated that some intervention used for teaching English during Covid-19 such as use of online tools such as video conferencing and social media platforms like WhatsApp and Facebook among others. Educators also took the advantage of Facebook platforms to engage their learners and coordinate class presentations and feedback obtained from the learners on work from each other on Facebook (Al-Jarf, 2021;Bayuong et al, 2019) Furthermore, Van Den Beemt et al (2020) found that there is increased use of social media among the learners that the educators have begun exploring the possible methods of introducing the use of social media in classrooms as well. Sivagnanam and Yunus (2020) added that social media can be used in the vocabulary enhancement as well as to engage the learners when educators instruct them to create English contents for their peers on platforms such as Facebook, Blogger and Twitter among others.…”
Section: Social Media In Esl Teaching and Learningmentioning
confidence: 99%
“…Considering that not much actual research has been undertaken so far (cf. Al-Jarf, 2021 ), this study therefore aims to investigate how some language teachers are making use of online teacher communities on Facebook for professional purposes amidst the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, based on the literature, it does not seem too much of a leap to assume that online communities may be particularly useful during crisis situations such as the pandemic when in-person interactions are difficult. Since the outbreak of COVID-19, there seems to be some evidence that teachers turned to these online communities (e.g., Al-Jarf, 2021 ; Carpenter et al, 2021 ; Trust et al, 2020 ). Considering that the pandemic has been one of the first serious global pandemics since the existence of online communities on SNSs, there is still a shortage of studies investigating how they can be used by language teachers in times of a pandemic for professional purposes.…”
Section: Introductionmentioning
confidence: 99%